The Influence of Product, Restaurant Atmosphere, Customer Value, and Customer Loyalty through Customer Statisfacation as Mediation (Case study on Choie Dimsum Surabaya) - Antikasari, Romadini; Baktiono, Agus; Arimbawa, I Gede; Damayanti, Elok (Quantitative Economics and Management Studies, 2021)
The purpose of this study was to analyze the effect of product quality, restaurant atmosphere, and customer value on customer satisfaction and customer loyalty. This type of research is quantitative. The population of this study were 95 respondents who bought at Surabaya Choie Dimsum. The analysis technique used is Partial Least Square (PLS). Data was obtained from questionnaires and tested with the SmartPLS 3.0 application. The results of this study indicate that product quality, restaurant atmosphere, and customer value have a positive and significant influence on customer satisfaction and customer loyalty. And customer satisfaction has a positive and significant influence on customer loyalty.